Teacher’s professional development of primary classes during the introduction to the profession - Поперечна, Леся (Pedagogy of Higher and Secondary Education, 2013)
Poperechna L. U. Teacher’s professional development of primary classes during the introduction to the profession. Survey was devoted to the actual topic, teacher’s professional development of primary classes in the period of introduction to the profession. The article presents a model of the organizational-pedagogical support the professional development of teacher of primary classes. The author explored the ways of managing professional development of teachers, analyzed the stages of entering of young teachers in the profession.